THE PROSPECTS OF DIGITAL ECONOMY IN UZBEKISTAN - Iroda Gayratovna Majidova (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the modern development of Internet commerce in the Republic of Uzbekistan